Aberrant DNA methylation of PTPRG as one possible mechanism of its under‐expression in CML patients in the State of Qatar - Mohamed A. Ismail; Muthanna Samara; Ali Al Sayab; Mohamed Alsharshani; Mohamed A. Yassin; Govindarajulu Varadharaj; Marzia Vezzalini; Luisa Tomasello; Maria Monne; Hisham Morsi; M. Walid Qoronfleh; Hatem Zayed; et al. (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Several studies showed that aberrant DNA methylation is involved in leukemia and cancer pathogenesis. Protein tyrosine phosphatase receptor gamma (PTPRG) expression is a natural inhibitory mechanism that is downregulated in chronic myeloid leukemia (CML) disease. The mechanism behind its downregulation has not been fully elucidated yet. Aim This study aimed to investigate the CpG methylation status at the PTPRG locus in CML patients. Methods Peripheral blood samples from CML patients at time of diagnosis [no tyrosine kinase inhibitors (TKIs)] (n = 13), failure to (TKIs) treatment (n = 13) and healthy controls (n = 6) were collected. DNA was extracted and treated with bisulfite treatment, followed by PCR, sequencing of 25 CpG sites in the promoter region and 26 CpG sites in intron‐1 region of PTPRG. The bisulfite sequencing technique was employed as a high‐resolution method. Results CML groups (new diagnosed and failed treatment) showed significantly higher methylation levels in the promoter and intron‐1 regions of PTPRG compared to the healthy group. There were also significant differences in methylation levels of CpG sites in the promoter and intron‐1 regions amongst the groups. Conclusion Aberrant methylation of PTPRG is potentially one of the possible mechanisms of PTPRG downregulation detected in CML.